Edge-selective decoration with ruthenium at graphitic nanoplatelets for efficient hydrogen production at universal pH. (October 2020) - Yang, Yejin; Kim, Jeongwon; Kim, Changmin; Seong, Arim; Kwon, Ohhun; Lee, Jeong Hyeon; Kristanto, Imanuel; Zhang, Linjuan; Zhou, Jing; Wang, Jian-Qiang; Baek, Jong-Beom; Kwak, Sang Kyu; et al.
Abstract: Although the electrochemical reaction is an effective and great promise to produce hydrogen, the realization of efficient and stable catalysts is still a significant challenge in the various electrochemical systems, such as water splitting and Zn-CO2 system. Herein, we report Ru nanoparticles anchored at edge-selectively nitrogenated graphitic nanoplatelets (Ru-ENG) instead of on the basal plane in two-dimensional (2D) graphitic substrate. The Ru nanoparticles interacted with both of armchair-ENG and zigzag-ENG substrate lead to favorable hydrogen evolution activities of icosahedron cluster Ru13 in Ru-ENG at a universal pH, compared to Ru metal cluster. The spontaneous electron re-construction between edge-site of N and ruthenium particles in Ru-ENG catalyst is attributed to the faster reaction kinetics with lower Tafel slopes and higher turnover frequencies than the benchmark Pt/C catalyst in any pH conditions. More importantly, the Ru-ENG electrocatalyst exhibited superior long-term consecutive stability (over 1, 500 h) at a high current density of 100 mA cm −2 in the practical water-splitting system. Graphical abstract: This work represents the edge-sites design of graphitic nanoplatelets with ruthenium nanoparticles for an efficient and stable HER electrocatalyst at universal pH. Image 1 Highlights: The Ru-ENG catalyst was designed with modification of edge sites of graphitic nanoplatelets induces high doping ratio without severing damages on the carbon basal plane. Interestingly, direct nitrogen(N) fixation at the broken edge sites of graphitic nanoplatelets was induced simply physicochemical radicalization process. Ru nanoparticles were self-grown with forming the N–Ru interaction at edge-sites of ENG and derived excellent catalytic activities. The X-ray absorption fine structure (XAFS) of Ru-ENG catalyst was placed between metallic Ru and RuO2, confirming the reconstructed electron configuration of metallic Ru on ENG. Notably, the Ru-ENG catalyst showed comparable Tafel slope for the HER comparing with the commercial Pt/C in a wide-pH window, along with stable performance over 1500 h for water splitting system.